Design of an integrated passive and active double facade system for UK offices - Kilaire, Aneel (2012)
The Egan Report, changes to Part L Building regulations, and the importance of office workers is challenging designers to improve the construction process, reduce operational carbon emissions, and enhance occupant comfort for office buildings in the United Kingdom. This thesis proposes a double skin facade system with integrated environmental systems to overcome these challenges. The Facade deals with a number of conflicting requirements and a single-storey, naturally ventilated cavity, unitised Double Facade has been proposed to resolve them. The two key determinants for the Active Environmental System have been prefabrication and operational carbon emissions. To address these issues a decentralised system, comprising of a Reversible Air Source Heat Pump, Heat Exchanger, Active Beam and Active Trench is proposed, and integrated into the Double Facade. A key part of the design process has been working with industrial partners to develop the design and realise a full-scale prototype. This has been tested and evaluated in terms of key aspects of the comfort, weather and aesthetic performance. An appraisal of the product demonstrates that it achieves proof of concept; it is highly prefabricated and enhanced occupant comfort and carbon emissions targets can be met.